Online Islamic Religious Education Learning During Covid-19 Pandemic - Nurdin Nurdin; Nurliana Nurliana; Saepudin Mashuri (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2022)
The Covid-19 pandemic has forced schools to carry out online learning. This study aims to determine the implementation of online learning and the challenges for teachers, students, and parents. This study uses a qualitative research method with a case study approach. Data were collected through observation, interviews, and written document studies. The data were analyzed using data reduction techniques, presentation, and verification. The results of this study indicate that the implementation of online learning at State Junior High School 1 Pasangkayu is less effective. The learning media used is the WhatsApp application with the assignment method in photos, documents, videos, and links. The problems faced by teachers in online learning are students' low interest in learning and lack of mastery of Information Technology. Meanwhile, the problem for students is that they cannot afford the internet quota and do not have an internet quota. They are bored, and their learning concentration is disturbed, they do not understand the material, the internet network is not stable. Problems for parents are low economic ability and low education level. The implication of this research is the need to apply online learning creatively and innovatively in presenting learning materials. In addition, it is also necessary to combine online and offline learning so that students who do not have an Android cellphone and a stable network can participate in learning during the pandemic.